2022
DOI: 10.1101/2022.04.12.488015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Goldilocks calcium and the mitochondrial respiratory chain: too much, too little, just right

Abstract: Calcium (Ca2+) is a key regulator in diverse intracellular signaling pathways, and has long been implicated in metabolic control and mitochondrial function. Mitochondria can actively take up large amounts of Ca2+, thereby acting as important intracellular Ca2+ buffers and affecting cytosolic Ca2+ transients. Excessive mitochondrial matrix Ca2+ is known to be deleterious due to opening of the mitochondrial permeability transition pore (mPTP) and consequent membrane potential dissipation, leading to mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, human colorectal cancer cells present lower maximal respiration in the absence of NCLX, but ATP-linked respiration is unaltered ( Pathak et al, 2020 ). In this sense, we have recently shown that optimal cytosolic and mitochondrial Ca 2+ concentrations are required to induce the expected enhancement of mitochondrial oxidative phosphorylation in liver mitochondria—both too much and too little result in lower electron transport capacity ( Vilas-Boas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, human colorectal cancer cells present lower maximal respiration in the absence of NCLX, but ATP-linked respiration is unaltered ( Pathak et al, 2020 ). In this sense, we have recently shown that optimal cytosolic and mitochondrial Ca 2+ concentrations are required to induce the expected enhancement of mitochondrial oxidative phosphorylation in liver mitochondria—both too much and too little result in lower electron transport capacity ( Vilas-Boas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their ability to take up, store, and release calcium (Ca 2+ ) in a regulated manner helps shape spatiotemporal features of Ca 2+ signaling events . Small and transient increases in Ca 2+ within mitochondria physiologically regulate both oxidative phosphorylation and the production of oxidants but can also mediate organellar damage when in excessive amounts Vilas-Boas et al 2022). Mitochondrial Ca 2+ uptake and release take place through independent pathways, and both activities are supported by protonmotive force .…”
Section: Introductionmentioning
confidence: 99%